Sustainable economic development and the environment: Theory and evidence - Luisito Bertinelli; Eric Strobl; Benteng Zou (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
The relationship between growth and pollution is studied through a vintage capital model, where new technology is more environmentally friendly. We find that once the optimal scrapping age of technologies is reached, an economy may achieve two possible cases of sustainable development, one in which pollution falls and another in which it stabilizes, or a catastrophic outcome, where environmental quality reaches its lower bound. The outcome will depend on countries' investment path and their propensity to innovate in environmentally clean technologies, both of which are likely to differ across economies. Empirical results using long time series for a number of developed and developing countries indeed confirm heterogeneous experiences in the pollution-output relationship.
urn:nbn:de:hbz:361-7349
Keywords: O13; Q01; Q55; 330; Environmental quality; Sustainable economic development; Vintage capital model; EKC (Environmental Kuznets Curve); Nachhaltige Entwicklung; Umweltbelastung; Umwelttechnik; Vintage-Modell; Environmental Kuznets Curve; Theorie